Sedimentology, structure and age estimate of five continental slope submarine landslides, eastern Australia. Issue 5 (3rd July 2016) - Clarke, S.; Hubble, T.; Webster, J.; Airey, D.; De Carli, E.; Ferraz, C.; Reimer, P.; Boyd, R.; Keene, J.; ,
ABSTRACT: Sedimentological and accelerator mass spectrometry (AMS) 14 C data provide estimates of the structure and age of five submarine landslides (∼0.4–3 km 3 ) present on eastern Australia's continental slope between Noosa Heads and Yamba. Dating of the post-slide conformably deposited sediment indicates sediment accumulation rates between 0.017 m ka –1 and 0.2 m ka –1, which is consistent with previous estimates reported for this area. Boundary surfaces were identified in five continental slope cores at depths of 0.8 to 2.2 m below the present-day seafloor. Boundary surfaces present as a sharp colour-change across the surface, discernible but small increases in sediment stiffness, a slight increase in sediment bulk density of 0.1 g cm –3, and distinct gaps in AMS 14 C ages of at least 25 ka. Boundary surfaces are interpreted to represent a slide plane detachment surface but are not necessarily the only ones or even the major ones. Sub-bottom profiler records indicate that: (1) the youngest identifiable sediment reflectors upslope from three submarine landslides terminate on and are truncated by slide rupture surfaces; (2) there is no obvious evidence for a post-slide sediment layer draped over, or burying, slide ruptures or exposed slide detachment surfaces; and (3) the boundary surfaces identified within the cores are unlikely to be near-surface slide surfaces within an overall larger en masse dislocation. These findings suggest that these submarine landslides are geologically recent (<25 ka), and that the boundary surfaces are either: (a) an erosional features that developed after the landslide, in which case the boundary surface age provides a minimum age for the landslide; or (b) detachment surfaces from which slabs of near-surface sediment were removed during landsliding, in which case the age of the sediment above the boundary surface indicates the approximate age of landsliding. While an earthquake-triggering mechanism is favoured for the initiation of submarine landslides on the eastern Australian margin, further evidence is required to confirm this interpretation.